IMPROVING COMMUNICATION SKILLS TO MITIGATE COUNTERPRODUCTIVE BEHAVIOR IN PROFESSIONAL SETTINGS - Jorovlea, Elvira (SWorldJournal, 2024)
Counterproductive work behavior (CWB) presents significant challenges for organizations, adversely affecting productivity and team dynamics. Key contributors to CWB include employee dissatisfaction and ineffective management practices. To mitigate these b